Un cimetière chinois dans la Somme : pratiques mémorielles, lieu de co-présence et territorialités diasporiques - Anne Hertzog; Rafiq Ahmad (Bulletin de l’Association de Géographes Français)
This paper highlights the process of “sinization” of a place that remains for a long time, in many ways, more “British” than “Chinese”, through the development of memorial practices within the Chinese diaspora in France. This process, however, is linked to other dynamics of appropriation, which are deployed at different scales. They reflect a great plurality of territorialization in memorial and heritage practices. The cemetery is thus built as a place of co-presence and a resource differently mobilized by different categories of actors.